Use of the Free Gingival Grafting Technique for soft tissue reconstruction after excision of a Peripheral Ossifying Fibroma (Research, Society and Development, 2021)
The Peripheral Ossifying Fibroma is a benign tumor that develops from a hyperplastic tissue reaction, usually related to traumatic stimulus that are responsible for triggering inflammatory reactions of the connective tissue. Histologically, it is a nodular mass characterized by a dense connective tissue, surrounded by stratified squamous epithelium. Surgical removal in these cases is indicated, and for reconstruction of soft tissue in the region, some periodontal surgical techniques are recommended, such as free gingival grafting. Thus, the present study aims to report a clinical case submitted to the free gingival graft technique for tissue reconstruction after the surgical removal of a fibroma. A total excision of the lesion was performed, later sent to a histopathological report where it was diagnosed as Peripheral Ossifying Fibroma, after the removal of the lesion the region was left with the periosteum exposed and then the free gingival graft was performed to cover the region and promote keratinized gum augmentation. This technique proved to be efficient for reconstruction of soft tissue in the region after surgical removal of the Peripheral Ossifying Fibroma, returning aesthetics, function and periodontal health.